2021
DOI: 10.15587/1729-4061.2021.238957
|View full text |Cite
|
Sign up to set email alerts
|

Development of brain tumor segmentation of magnetic resonance imaging (MRI) using U-Net deep learning

Abstract: Brain tumors are the growth of abnormal cells or a mass in a brain. Numerous kinds of brain tumors were discovered, which need accurate and early detection techniques. Currently, most diagnosis and detection methods rely on the decision of neuro-specialists and radiologists to evaluate brain images, which may be time-consuming and cause human errors. This paper proposes a robust U-Net deep learning Convolutional Neural Network (CNN) model that can classify if the subject has a tumor or not based on Brain Magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…From a comparison between the developed method and recent studies such as the studies [17,22] that used Cystoscopic images with U-Net CNN, and the study [19] that used MRI images with transfer deep learning, the developed Inception-v3 architecture achieved better accuracy. Furthermore, it is found that the AUC for the true positive rate with respect to the false positive rate is around 1 for the dataset considered in this study (Table 1).…”
Section: Discussion Of the Results Of Classifying Tumor Images Using ...mentioning
confidence: 97%
“…From a comparison between the developed method and recent studies such as the studies [17,22] that used Cystoscopic images with U-Net CNN, and the study [19] that used MRI images with transfer deep learning, the developed Inception-v3 architecture achieved better accuracy. Furthermore, it is found that the AUC for the true positive rate with respect to the false positive rate is around 1 for the dataset considered in this study (Table 1).…”
Section: Discussion Of the Results Of Classifying Tumor Images Using ...mentioning
confidence: 97%
“…The Laplace transform and deep learning CNN solutions show excellent consistency for the steady solutions and there is a good agreement between the obtained transients. Future work can be recommended when comparing the solving of such symbolic differential equations of the 2-loop RLC AC circuit with deep learning convolutional neural network [33], [34].…”
Section: Laplace Transform Resultsmentioning
confidence: 99%
“…It is proposed to use the U-Net CNN [15,16] to segment images of objects in aerial photographs. To improve the efficiency of the neural network, this model was trained by a set of aerial photographs (Fig.…”
Section: Discussion Of Results Of Studying the Semantic Segmentation Of Images Of Objects In Aerial Photographs Using Cnnmentioning
confidence: 99%
“…Our review of the literature [15,16] showed that the U-Net model demonstrates high efficiency for the semantic segmentation of images of objects of different shapes and positions.…”
Section: Literature Review and Problem Statementmentioning
confidence: 97%